2017
DOI: 10.3892/ol.2017.6224
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations in Japanese extrahepatic biliary tract cancer

Abstract: Abstract. Biliary tract cancer (BTC) is one of the most devastating types of malignant neoplasms worldwide. However, the mechanisms underlying the development and progression of BTC remain unresolved. BTC includes extrahepatic bile duct carcinoma (EBDC), gallbladder carcinoma (GBC)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
0
14
2
Order By: Relevance
“…No instances of ARID1A or PIK3CA mutations were observed in the Japanese patient cohort, which contrasts with one report identifying inactivating ARID1A mutations in Japanese patients . In contrast, other reports using sequencing assays failed to find ARID1A mutations among Asian patients . In addition, TP53 mutations were more prevalent in the Chilean cohort (76%), although this difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 89%
See 3 more Smart Citations
“…No instances of ARID1A or PIK3CA mutations were observed in the Japanese patient cohort, which contrasts with one report identifying inactivating ARID1A mutations in Japanese patients . In contrast, other reports using sequencing assays failed to find ARID1A mutations among Asian patients . In addition, TP53 mutations were more prevalent in the Chilean cohort (76%), although this difference did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 89%
“…38 In contrast, other reports using sequencing assays failed to find ARID1A mutations among Asian patients. 37,40,41 In addition, TP53 mutations were more prevalent in the Chilean cohort (76%), although this difference did not reach statistical significance. Prior reports have noted that TP53 mutations occur in 47% to 64% of patients.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…While no PIK3CA mutations were found in Brazil patients, 12.5%, 16.9%, and 21.4% of GBC with PIK3CA mutations were identified in USA, Japan, and Chile, respectively. 154,[203][204][205] We previously found that PIK3CA mutations E545K occurred in~5.9% of GBC, and that these patients exhibited a worse prognosis. 58,206 Epigenetic alteration of PTEN also contributes to the development of GBC as 30% GBCs exhibited PTEN promoter hypermethylated.…”
Section: Her2mentioning
confidence: 99%